Court interpreting in England: what works? (and for whom)? : how Interpreted Prison Video Link impacts upon courtroom interaction - Fowler, Yvonne (Language and Law / Linguagem e Direito, 2017)
All defendants who do not speak the language of the court are at a disadvantage. This article considers how the impact of two factors upon the quality of interpreting in our courts might confer additional disadvantage. Firstly it considers the contracting out of interpreting services to private companies, whose main consideration is prot rather than competent interpreting or justice for the defendant, a political dimension often ignored by interpreting scholars. Secondly it explores diering viewpoints and perceptions of interpreted court hearings by ve groups of participating court actors where prisoners appear in court via video link from prison. Using in-depth interviews, audio-recordings of court hearings and ethnographic observation, these diering perceptions will be used to provide vignettes of court hearings and prisoners as they appear remotely, dependent upon the interpreter’s renditions to orientate themselves to court proceedings. Finally, training and a best practice protocol for court actors and interpreters is suggested.